Implementation Of Tanah Laut District Regional Regulation Number 6 Of 2022 Concerning The Implementation Of Social Welfare - Maigina Azizah; Bahran (Interdisciplinary Explorations in Research Journal, 2024)
Abstract Social welfare is the most desired part of human life because it exists to help individuals escape from all social problems. Therefore, it is necessary to implement social welfare as a government effort in the form of social services to meet the basic needs of every citizen. This research discusses the extent of implementation of Tanah Laut Regency Regional Regulation Number 6 of 2022 concerning the Implementation of Social Welfare in dealing with social problems in Tanah Laut Regency, as well as knowing the supporting and inhibiting factors for the Tanah Laut Regency government in handling social problems in Tanah Laut Regency. This research uses a legal sociology approach, namely studying and analyzing the rules that operate in society. The results of this research show that the Tanah Laut Regency Regional Regulation Number 6 of 2022 has been implemented well by the government in accordance with their respective duties and functions. In organizing social welfare, there are supporting and inhibiting factors, namely: supporting factors such as human resources, facilities and infrastructure as well as supporting funds, while the inhibiting factors are the lack of social institutions, halfway houses and proper logistics warehouses, and there is a lot of data on recipients of social assistance. which is invalid can cause social assistance to be inappropriately targeted. Keywords :Implementation , Regional Regulations, Social Welfare Abstract Kesejahteraan Sosial adalah bagian yang paling diharapkan dari kehidupan manusia karena terwujud untuk membantu agar individu terlepas dari segala permasalahan sosial. Maka dari itu perlu penyelenggaraan kesejahteraan sosial sebagai upaya pemerintah dalam bentuk pelayanan sosial guna memenuhi kebutuhan dasar setiap warga negara. Penelitian ini membahas tentang sejauh mana implementasi Peraturan Daerah Kabupaten Tanah Laut Nomor 6 Tahun 2022 Tentang Penyelengaraan Kesejahteraan Sosial dalam menangani permasalahan sosial di Kabupaten Tanah Laut, serta mengetahui faktor pendukung dan faktor penghambat bagi pemerintah Kabupaten Tanah Laut dalam menangani Permasalahan Sosial di Kabupaten Tanah Laut. Penelitian ini menggunakan pendekatan sosiologi hukum, yaitu mengkaji dan menganalisis terkait aturan yang berjalan di masyrakat. Hasil penelitian ini menunjukan bahwa Peraturan Daerah Kabupaten Tanah Laut Nomor 6 Tahun 2022 sudah dijalankan dengan baik oleh pemerintah sesuai dengan tugas dan fungsi masing-masing. Dalam menyelengarakan kesejahteraan sosial ini terdapat faktor pendukung dan penghambatnya yaitu: faktor pendukungnya seperti SDM, Sarana dan prasarana serta dana yang mendukung, sedangkan faktor penghambatnya ialah belum adanya panti sosial, rumah singgah dan Gudang logistic yang layak, dan banyak terdapat beberapa data penerima bantuan sosial yang tidak valid singga menimbulkan bantuan sosial tersebut menjadi tidak tepat sasaran. Kata Kunci: Implementasi, Peraturan Daerah, Kesejahteraan Sosial.